Falling for you - Schroeder, Lisa (Simon Pulse, 2013)
Very good friends, her poetry notebooks, and a mysterious "ninja of nice" give seventeen-year-old Rae the strength to face her mother's neglect, her stepfather's increasing abuse, and a new boyfriend's obsessiveness.